(untitled) (Journal of Hama University, 2024)
This research aims to measure and analyze competitiveness, and measure financial stability of conventional and Islamic banks operating in Syria during the period (2009-2019), and then test the impact of competitiveness on the stability of these banks. To achieve the objectives of the research, banking concentration ratio (CRk (and Herfindahl-Hirschman index (HHI) were used as structural measures of competitiveness, and Panzar-Rosse approach (P-R) was used as non-structural measure of competitiveness. In addition to that, Z-Score index was used to measure financial stability in banks under study. Panel Data models were used to calculate Panzar-Rosse’s H- statistic value to measure competitiveness and to test the impact of competitiveness on financial stability. The research concluded that competitiveness in Syrian banking sector is weak, which confirmed by the result of structural and non-structural measures, according to structural measures, the avarege banking concentration ratio of the four largest banks CR4 in relation to total assets, deposits, and loans was 74.6%, 70.7%, and 77.2% respectively, these results were supported by (HHI), as its value exceeded 1800 for each of the assets, deposits, and loans, which indicate the high concentration in Syrian Banking sector and the low competitiveness of other banks to increase their market share. The reaserch also concluded that competitiveness according to (P-R) is weak, and there is a state of monopolistic competition in Syrian banking sector, as the average H-statistic value during the study period was 0.024, wich reflect a low degree of competitiveness. According to monopolistic competition, there are a few dominant banks in the banking market, while the rest of the banks don’t have a competitive ability to confront it. In addition, when calculating the value of Z-SCORE, a state of financial stability was reached in those banks, as the average value of the index was 5.07, and this value considered good and evidence of the stability of the banks, the reaserch also concluded that competitiveness does not have any impact on financial stability of Syrian banking sector.